A Hybrid Intelligent System for Diagnosis of Diabetes - Bani Amer, Mashhour M.; Alghawli, Abed Saif (Discoveries in Agriculture and Food Sciences, 2014)
This paper presents a hybrid intelligent system for diagnoses of diabetes. It is based on neuro-fuzzy inference system which is trained and tested using experimental data collected from two hundred different patients. The main clinical feature of this system is that it can be used by a patient’s smart phone, Pocket PC or PDA to provide local diagnosis of blood glucose level and to transmit the captured data to a remote hospital or clinician for assistance and medical advice. The performance of the system was tested and the results showed that it is capable to diagnose the diabetes with a high degree of precision.